Comprehensive Evaluation of Quality of Life following Upper Eyelid Blepharoplasty: A Prospective Analysis - Dolika D. Vasović; Miodrag Lj. Karamarković; Milan Jovanović; Milan Stojičić; Dejan M. Rašić; Ivan Marjanović; Tanja Kalezić; Miroslav Jeremić (Medicina, 2024)
Background and Objectives: Upper eyelid blepharoplasty is a surgical procedure that addresses both aesthetic and functional concerns, offering transformative potential for patients’ overall well-being. This study systematically evaluates the comprehensive impact of upper eyelid blepharoplasty on patients’ quality of life, employing rigorous methodologies and standardized assessment protocols. Materials and Methods: A prospective, randomized controlled trial was conducted, involving 348 patients aged 49 to 87 years. Patients were randomly assigned to receive either continuous or intradermal sutures following upper eyelid surgery. Validated FACE-Q questionnaires were used to assess various outcomes, including early-life impact, expectations, satisfaction with eyes, overall face satisfaction, satisfaction with the outcome, psychological function, social function, and adverse effects. Results: Results indicate significant improvements in multiple domains of patient-reported outcomes following upper eyelid blepharoplasty, including satisfaction with eyes, overall face satisfaction, satisfaction with the outcome, psychological function, and social function. Notably, no significant differences were observed between suturing techniques regarding patient satisfaction and well-being. Adverse effects were minimal and improved over time. Conclusions: The study underscores the transformative nature of upper eyelid blepharoplasty in enhancing patients’ quality of life, addressing both cosmetic and functional concerns. Utilizing standardized assessment tools like the FACE-Q questionnaire facilitates a comprehensive understanding of treatment outcomes and enables patient-centered care. Overall, this research contributes to the growing evidence supporting the positive impact of upper eyelid blepharoplasty on patients’ well-being, emphasizing the importance of continued research and standardized assessment protocols in advancing patient care in cosmetic surgery.